Counseling psychologists in medical education in the United States: career development, professional identity, and training implications. Issue 2 (2nd April 2020) - Raque-Bogdan, Trisha L.; Ratchford, Julia L.; Garriott, Patton O.; Borges, Nicole J.; Duffy, Ryan D.
ABSTRACT: Psychologists have been working in medical education for over 100 years and the number of psychologists in these settings is increasing, yet the involvement of counseling psychologists in medical education remains largely undocumented. This qualitative study utilized Consensual Qualitative Research Methodology to analyze the career development, work experiences, and professional identity of 10 counseling psychologists currently working in the field of medical education in the United States. The five domains that emerged from the data were: (1) career path, (2) adaptation of one's professional identity into medical education, (3) complimentary aspects of counseling psychology and medical education, (4) challenges of working as a counseling psychologist in medical education, and (5) training implications. Results indicated the potentially unique contributions counseling psychologists can make in American medical education teaching, training and supervision, behavioral health interventions, and culturally sensitive healthcare. Challenges included establishing legitimacy as they navigated the medical hierarchy. Implications for practice and training related to interprofessional settings are presented.